Ferrocene-containing β-diketones derived from lactones: synthesis, complexation with rhodium(I), electrochemistry and substitution kinetics - Siegert, Lydia (University of the Free State, 2016)
New ferrocene-containing β-diketones of the form FcCOCH2CO(CH2)nOH (Fc = ferrocenyl) where n = 3 [pKa' = 5.97], 4 [pKa' = 8.01] and 5 [pKa' = 10.44] were prepared by the Claisen condensation of acetyl ferrocene and the appropriate cyclic ester under the influence of lithium diisopropylamide. The rate of conversion of FcCOCH2CO(CH2)5OH from the enol to the keto form and vice versa was studied and the kinetic parameters determined. All β-diketones were also reacted with [Rh2(COD)2Cl2] to yield the [Rh(β-diketonato)(COD)] complexes [Rh(FcCOCHCO(CH2)nOH)(COD)] where n = 3, 4 and 5. The group electronegativity of the alcohol side chains was determined by the linear relationship between the methyl or ethyl ester (RCOOMe or RCOOEt) infrared carbonyl stretching frequencies and the group electronegativities of known R groups, R = CF3, CCl3, CH3, C6H5 and Fc. A cyclic voltammetry study of the free β-diketones showed chemical and quasi-electrochemically reversible behaviour for the iron core in the free β-diketones with side-chain lengths of 3, 4 and 5 carbons with E0ˊ = 197 mV, 174 mV and 151 mV respectively. Electrochemical and chemical reversibility were observed for the ferrocene moiety during the study of the [Rh(β-diketonato)(COD)] complexes. It was found that the rhodium centre of the rhodium complexes exhibited two coordination numbers. A 4-coordinate rhodium redox centre was observed with ipc/ipa. >1 and ΔE < 100 mV. Electrochemical evidence of a 5-coordinate rhodium centre by virtue of interaction between the OH-endgroups of the side-chain of the β-diketonato ligand and the rhodium centre, was observed. Substitution of the β-diketonato ligand from the [Rh(β-diketonato)(COD)] complexes with 1,10- phenanthroline in methanol was also studied and the kinetic parameters determined. Large negative activation entropy values were obtained; these suggested an associative substitution mechanism. All substitution reactions had observable mechanistic solvent pathway contributions.

Deur middel van Claisen-kondensasie van asetielferroseen met die ooreenstemmende sikliese esters onder die invloed van litiumdiisopropielamied, is nuwe ferroseen-bevattende β-diketone, FcCOCH2CO(CH2)nOH (Fc=ferroseniel) waar n = 3 [pKa' = 5.97], 4 [pKa' = 8.01] en 5 [pKa' = 10.44], gesintetiseer. Die reaksie tempo van omskakeling vanaf die enol vorm na die keto toestand en ook omgekeerd is betudeer vir FcCOCH2CO(CH2)5OH met behulp van 1H KMR spektroskopie. Kinetiese parameters is dus bereken. Die rhodium komplekse, [Rh(FcCOCHCO(CH2)nOH)(COD)] waar n = 3, 4 en 5, is berei deur die ooreenstemmende β-diketoon met [Rh2(COD)2Cl2] te reageer. Die skynbare groep elektronegatiwiteite van die alkohol sy-kettings is bepaal vanaf die lineêre verband tussen die metiel of etiel esters (RCOOMe of RCOOEt) se infrarooi karbonielstrekkingsfrekwensies en die groep elektronegatiwiteit van bekende R groepe, R = CF3, CCl3, CH3, C6H5 en Fc. Die sikliese voltammetries bepaalde formele reduksiepotensiale, E0ˊ, vir die ferrosenielgroep van die β-diketone met sy-ketting lengtes van 3, 4 en 5 koolstowwe is gevind as E0ˊ = 197 mV, 174 mV en 151 mV onderskeidelik. Chemiese en quasi-elektrochemiese omkeerbaarheid is bevind. Tydens die elektrochemiese studie van die [Rh(β-diketonato)(COD)] komplekse, is chemiese en elektrochemiese omkeerbaarheid vir die ferroseniel groep opgemerk. Dit is gevind dat die rhodium kern in die rhodium komplekse twee verskillende koördinasie getalle openbaar: ‘n 4-gekoördineerde rhodium redoks paar is waargeneem met ipc/ipa. >1 en ΔE < 100 mV, en as gevolg van interaksie tussen die OH terminale groep en die rhodium kern, is ‘n 5-gekoördineerde rhodium redoks paar ook waargeneem. Substitusiekinetika van die bidentate β-diketone in die [Rh(β-diketonato)(COD)] komplekse met behulp van 1,10-fenantrolien is spektrofotometries (UV/vis) ondersoek. Relatiewe groot aktiveringsentropie dui op ‘n assoiatiewe meganisme. Alle substitusie reaksies het ‘n beduidende oplosmiddelroete komponent in die meganisme getoon.
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2016
Keywords: Metallocenes; β-diketones; Rhodium; Isomerization; Kinetics; Cyclic voltammetry; Substitution kinetics